PAKISTAN AND THE PLANET: A ROLE IN GLOBAL CLIMATE DYNAMICS - Muzakir Khan; Kiramat Ullah; Muhammad Haroon; Dr. Asif Ali (`, 2024)
The phenomenon of climate change is one that must be confronted on a global scale as it poses a threat that is not only diverse but also pressing with a number of nations being either part of the problem or part of the solution. Pakistan finds itself at a critical moment as it is working alongside the global community while tackling dire climate issues such as floods, severe heat waves and droughts. This paper looks at a more Pakistan focused approach by examining the nation’s perspective on two facets of the problem: first, its role in causing climate change and secondly, its impact on the country that has now become Pakistan’s reality. It explains the primary sources of greenhouse gas emissions in Pakistan while placing them into context with other countries namely energy generation, agriculture, processes of deforestation, growing demographics and construction. These geographical characteristics make Pakistan more vulnerable to climate effects that come along with the Himalayan glaciers and the Indus River basin which include water shortages, food insecurity, and flooding, displacement and health issues. The paper further discusses renewable energy programs along with improved energy efficiency approaches and Pakistan’s strategy for disaster management as measures that the nation plans to take in responding to climate change. At the international level, Pakistan is insisting on climate change financing and technology from developed countries while gauging the implications of treaties like the Paris Agreement for the implementation of its domestic policies. This research assesses Pakistan’s climate action policies, the success or challenges surrounding those plans, and simply how Pakistan has managed to integrate or rather contribute into the global fight against climate change. Keywords: Climate Change, Pakistan’s Vulnerability, Greenhouse Gas Emissions, Mitigation and Adaptation, Paris Agreement